2004
DOI: 10.1021/es049787+
|View full text |Cite
|
Sign up to set email alerts
|

Search for the Contamination Source of Butyltin Compounds in Wine:  Agglomerated Cork Stoppers

Abstract: A possible butyltin contamination source in wine was studied in this paper. Agglomerated cork stoppers, which were produced in Portugal, Spain, and Italy, used in wine bottles were examined. The domestic cork products, cork granules, and mucus used for cork products were also analyzed. The levels of mono-and dibutyltin compounds in corks were found in the range from <0.0024 to 3.3 and from <0.0029 to 6.7 µg of Sn/g, respectively. A low level of tributyltin contamination was also found in 2 of 31 tested samples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…The neurotoxic presentation most frequently reported in human cases is a limbic-cerebellar syndrome, the manifestations of which include memory defects, confusion, seizures, tinnitus, insomnia, and depression (Saary and House, 2002). Despite the documented presence of TMT in aquatic environments (Jiang et al, 2004; Jiang et al, 2001; Liu and Jiang, 2002; Shawky and Emons, 1998; Zhou et al, 2001) its potential risk to aquatic organisms is largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…The neurotoxic presentation most frequently reported in human cases is a limbic-cerebellar syndrome, the manifestations of which include memory defects, confusion, seizures, tinnitus, insomnia, and depression (Saary and House, 2002). Despite the documented presence of TMT in aquatic environments (Jiang et al, 2004; Jiang et al, 2001; Liu and Jiang, 2002; Shawky and Emons, 1998; Zhou et al, 2001) its potential risk to aquatic organisms is largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Butyltin contamination in wine may come from sources such as agglomerated cork stoppers. Jiang et al (2004) found that all overseas agglomerated cork stoppers investigated contained mono-and/or dibutyltin, which were not present in domestic agglomerated cork products.…”
Section: Distribution Of Organotins In Other Foodsmentioning
confidence: 89%
“…Levels found in wine are higher than other alcoholic drinks, likely due to acidity-enhanced migration from PVC FCM [90]. Another possible source for organotins in wines are the closures [106].…”
Section: Organotinsmentioning
confidence: 98%